APLIKASI ENKRIPSI DAN DESKRIPSI DATA MENGGUNAKAN ALGORITMA RC4 DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN PHP - Elka Lukman Hakim; Khairil Khairil; Ferry Hari Utami (Jurnal Media Infotama, 2014)
Security and confidentiality of data is currently a very important issue and continues to grow. Some cases involving data security is now a job that requires handling and security costs so much. To maintain the security and confidentiality of messages, data, or information that cannot be read or understood by any person, except for recipients who are entitled, then the application of a safety system designed by the method of data encryption using the RC4 algorithm.RC4 (Rivets Cipher 4) is a Synchrony stream cipher, which has a symmetric key cipher and encrypt the plaintext digits are digits per byte by byte or by combining with a binary operation XOR with a random number.Keywords: Encryption, RC4, XOR Operation